A fire spread simulator to support tactical management decisions for Mediterranean landscapes - Gonzalez-Olabarria, Jose Ramon; Carrasco, Jaime; Pais, Cristobal; Garcia-Gonzalo, Jordi; Palacios-Meneses, David; Mahaluf-Recasens, Rodrigo; Porkhum, Olena; Weintraub, Andrés (Frontiers in Forests and Global Change, 2023)
The use of fire simulation tools has become a regular feature of support systems for fuel management decisions at landscape level. Considering the spatial nature of fire in the evaluation of risk and the definition of fire mitigation goals is an ongoing research topic in forest management planning. By combining a fire simulation tool, a growth and yield simulator and an optimization module, it is possible to minimize the negative impact of fire over time and maximize the yield of various ecosystem services. Specific requirements for a fire simulator adapted to support tactical forest planning include a level of accuracy, the possibility of exploring diverse fire scenarios, the computational capability to simulate multiple fires and the flexibility to generate different outputs or metrics depending on the specific requirements of the planning problem under study. The present article addresses the requirements of fire simulators for their inclusion on forest tactical planning. The Cell2Fire simulator is adapted for use with fuel models more commonly employed in Europe and the United States, and to simulate the generation and spread of crown fires. Already able to solve static fire mitigation problems in its original version, this new adaptation, known as Cell2Fire_SB, has been developed with the more ambitious goal of being integrated into a decision support system that simultaneously considers fire behavior forest dynamics and allocation of management actions in order to solve temporal dynamic tactical forest problems.